Toward a Comparative Approach to Language Acquisition. (April 2022) - Christiansen, Morten H.; Contreras Kallens, Pablo; Trecca, Fabio
The world's languages vary in almost every conceivable way, yet children readily learn their native language. Understanding how children can acquire such a diversity of different languages has been a long-standing goal for psychological science, yet current acquisition research is dominated by studies of children learning one particular language: English. In this article, we argue that progress toward this goal will require systematic comparisons between different languages. We propose three levels of comparison: coarse-grained comparisons contrasting unrelated languages to confirm or refute broad theoretical claims, fine-grained comparisons between closely related languages to investigate the impact of specific factors on acquisition outcomes, and within-language comparisons targeting the impact of socio-communicative differences on learning. This three-pronged comparative approach to language acquisition promises to provide new insights into the mechanisms and processes by which children acquire their native tongue under such varied linguistic and socio-communicative conditions.